2023
DOI: 10.3390/ijms241310649
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Matrix Metalloproteinases and Their Natural Inhibitors in Metabolism: Insights into Health and Disease

Abstract: Matrix metalloproteinases (MMPs) are a family of zinc-activated peptidases that can be classified into six major classes, including gelatinases, collagenases, stromelysins, matrilysins, membrane type metalloproteinases, and other unclassified MMPs. The activity of MMPs is regulated by natural inhibitors called tissue inhibitors of metalloproteinases (TIMPs). MMPs are involved in a wide range of biological processes, both in normal physiological conditions and pathological states. While some of these functions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 251 publications
2
13
0
Order By: Relevance
“…Opinions about TNF-alpha are divided, as Russell et al found that obese adolescent girls have an increased level of TNF-α receptors, which would enable TNF-α to bind more easily to its receptor and have a greater effect (such as IL-6 stimulation) without the need to increase the circulating TNF-α concentration [ 35 ]. TIMP-2 is ubiquitously, constitutively expressed protein that acts as a highly effective inhibitor of multiple MMPs including MMP-2 and MMP-9 [ 36 ]. TIMP-2 is also highly expressed in leukocytes [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Opinions about TNF-alpha are divided, as Russell et al found that obese adolescent girls have an increased level of TNF-α receptors, which would enable TNF-α to bind more easily to its receptor and have a greater effect (such as IL-6 stimulation) without the need to increase the circulating TNF-α concentration [ 35 ]. TIMP-2 is ubiquitously, constitutively expressed protein that acts as a highly effective inhibitor of multiple MMPs including MMP-2 and MMP-9 [ 36 ]. TIMP-2 is also highly expressed in leukocytes [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…MMP-12 is primarily secreted by activated macrophages and exhibits high specificity for elastin degradation. Recent observations suggest that that increased expression of MMP-12 by M2 macrophages in adipose tissue of obese subjects may be a compensatory mechanism to restrain adipose tissue expansion and insulin resistance [ 36 ]. Found here increased plasma leptin level and its strong positive correlation with liver inflammatory marker, GGTP (r = 0.964) suggest that leptin may induce pro-inflammatory reactions reflected by hepatocyte as an element of progressive, but still discrete inflammatory response in children with simple obesity.…”
Section: Discussionmentioning
confidence: 99%
“…Obesity involves 170 million children (under the age of 18) and 650 million adults, with growing prevalence in low-and middle-income countries [52]. Obesity complications include type 2 diabetes mellitus (T2DM), thyroid diseases, hypertension, cancer, and depression, representing a worldwide concern both for the negative impact on the quality of life and for the associated elevated annual health-care costs [53].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, irisin, as happens with MMPs, shows a different expression pattern depending on the study model, the stage of maturation, and the tissue location of adipose cells, and these aspects create many difficulties in gaining a full and complete understanding of its intrinsic clinical significance [40,41,52].…”
Section: Introductionmentioning
confidence: 99%
“…Zinc finger proteins can act as transcription factors that regulate HSCs activation, mitochondrial autophagy, the inflammatory response, and glucose-lipid metabolism, which influence MAFLD progression (Figure 1) [245][246][247][248][249]. In addition, zinc is a key component of matrix metalloproteinases (MMPs) that degrade the extracellular matrix, of which upregulated MMP14 and inactivated MMP11 are associated with hepatic steatosis, while upregulated MMP2 and MMP9 are associated with hepatic fibrosis and inflammation, respectively [250]. The coexistence of hepatic zinc deficiency and iron accumulation contributes to the development of hepatic fibrosis, which may be related to extracellular matrix remodeling and changes in lipid composition [251].…”
Section: Zinc Metabolism and Mafldmentioning
confidence: 99%